THE INTERPLAY OF READING ANXIETY, READING STRATEGY USE AND ACADEMIC ACHIEVEMENT OF NON-ENGLISH MAJORED STUDENTS AT A UNIVERSITY IN THE NORTH OF VIETNAM - Dung, Le Quang (VNU Journal of Foreign Studies; Vol 36 No 6DO - 10.25073/2525-2445/vnufs.4629, 2020)
A quantitative research was carried out at the International School, Thai Nguyen University to measure the levels of reading anxiety among non-English majored students who had just finished one year of intensive English. These students were supposed to take a simulation IELTS exam with an expected result of 5.5 overall bands (B2-CEFR). The finding showed that the level of anxiety measured was at medium level (M = 3.31, SD = 0.59, SEM = 0.09, Min = 2.05, Max = 4.30, Skewness = -0.46, Kurtosis = -0.54). The second research question focuses on the correlation between reading anxiety and the use of reading strategies. The results showed that there was no significant difference between reading anxiety and the uses of reading strategies. The third research finding indicated that there was a significant difference between the levels of reading anxiety and academic reading achievement. Students with high level of anxiety attain low achievement. Low anxiety ( M = 2.64, SD = 0.50) was significantly larger than for High anxiety ( M = 1.40, SD = 0.52).